2021
DOI: 10.1515/jcim-2019-0212
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fennel on primary dysmenorrhea: a systematic review and meta-analysis

Abstract: BackgroundOne of the most common complaints for women is dysmenorrhea. Several studies investigated the treatment effects of medicinal plants on primary dysmenorrhea.ObjectivesThis systematic review and meta-analysis investigates the effect of Foeniculum vulgare (Fennel) on pain in primary dysmenorrhea in comparison to non-steroidal anti-inflammatory drugs such as mefenamic acid.MethodsPubMed, EMBASE, EBSCO Web of Science, Scopus, Cochrane library, Cochrane Central Register of Controlled Trials (CENTRAL), Scie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Twelve clinical trials were included in the analysis, and the results showed that ingestion of fennel extracts significantly (p < 0.01) reduced the pain intensity of dysmenorrhea as compared with placebo. The effect of fennel versus mefenamic acid did not differ, suggesting that fennel supplements were as effective as mefenamic acid 48 . Thus, these results support the MTM use of fennel for dysmenorrhea.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Twelve clinical trials were included in the analysis, and the results showed that ingestion of fennel extracts significantly (p < 0.01) reduced the pain intensity of dysmenorrhea as compared with placebo. The effect of fennel versus mefenamic acid did not differ, suggesting that fennel supplements were as effective as mefenamic acid 48 . Thus, these results support the MTM use of fennel for dysmenorrhea.…”
Section: Resultsmentioning
confidence: 89%
“…In terms of premenstrual syndrome (PMS), clinical data suggests that oral administration of a fennel extract reduced the symptoms of PMS including stress, cluster and somatic symptoms, excitement, and depression 46,47 . One meta-analysis investigated the effects of fennel on pain associated with primary dysmenorrhea and compared these data with that of mefenamic acid 48 . Twelve clinical trials were included in the analysis, and the results showed that ingestion of fennel extracts significantly (p < 0.01) reduced the pain intensity of dysmenorrhea as compared with placebo.…”
Section: Resultsmentioning
confidence: 99%
“…F. vulgare is an umbelliferous plant, the fruit, and root infusions of which are used for estrogenic, relaxant, analgesic, and anti‐inflammatory purposes. It has been reported to promote female problems such as menstruation, facilitate birth, increase milk secretion, and libido and lessen the symptoms related to dysmenorrhea and climacteric (Choi & Hwang, 2004; Ostad et al, 2001; Shahrahmani et al, 2021). Further, seed extract of this plant has been claimed to show estrogenic, antioxidant, and anti‐hirsutism actions (Oktay et al, 2003) and is useful in the discharging of vasomotor symptoms, sexual function, vaginal dryness, itching, dyspareunia, and sleep distribution related to menopause.…”
Section: Management Of Menopause and Related Disordersmentioning
confidence: 99%
“…Therefore the results suggest that Thymus vulgaris and ibuprofen effectively reduce pain intensity in primary dysmenorrhea. Similarly, Shahrahmani et al (53) recently carried out a meta-analysis that compared the effects of Foeniculum vulgare and mefenamic acid on primary dysmenorrhea. The study revealed that the intake of F. vulgare significantly decreased the intensity of dysmenorrhea compared to the placebo.…”
Section: Natural Productsmentioning
confidence: 99%